Psychological Pollution among Jordanian Unemployed Faculty of Education Graduates in Public and Private Universities - Nizar Mohammed Al - Zubi (College of Education for Women, 2018)
Abstract The aim of the study was to examine the level of psychological pollution among Jordanian unemployed faculty of education graduates in public and private universities. The sample of the study consisted of (413) Jordanian male and female unemployed faculty of education graduates in 2017. The researcher administrated the psychological pollution scale on the sample of the study, consisting in the final format of (37) items distributing on (4) domains. Validity and reliability for the scale were obtained. The results of the study indicated that level of psychological pollution among Jordanian unemployed faculty of education graduates in public and private universities was high (M=3.48, SD=0.83). The results of the study indicated apparent differences on the total items of the psychological pollution scale among Jordanian unemployed faculty of education graduates in public and private universities due to gender, in favor of males; due to marital status, in favor of singles, while no differences were found due to university and years of unemployment. The results of the study indicated a statistically significant difference (α=0.05) in students means scores on all the scale domains due to gender, in favor of males; due to marital status, in favor of singles, while no  statistically significant differences (α=0.05)  were found  on total psychological pollution scale domains due to university and years of unemployment. The study presented some recommendations.